Pregnancy and lambing rates following direct transfer of vitrified embryos in field ewes of Bangladesh - Islam, Md Monirul; Talukder, Mohammad Rafiqul Islam; Naher, Nazmun; Jha, Pankaj Kumar; Bhuiyan, Mohammad Musharraf Uddin; Bari, Farida Yeasmin (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: Embryo vitrification facilitates multiple ovulation and embryo transfer (MOET) application in the sheep industry through the storage and transfer of genetically superior embryos. This study assessed the survival rate of vitrified embryos following direct transfer under field conditions. Materials and Methods: Thirty-five donors and 46 recipient ewes were synchronized for estrus using two injections of Cloprostenol. Superovulation was induced with 25 mg porcine follicle-stimulating hormone per donor twice daily for 4 days. Recipients were treated with 250 IU of pregnant mare serum gonadotrophin during the second injection of cloprostenol to ensure ovulation. Estrus donors were mated with rams. Embryos were collected on day 6 post-mating using a modified inguinal laparotomy and graded. Grade 1 embryos were vitrified in a medium containing tissue culture medium 199, 10% ethylene glycol, 10% dimethyl sulfoxide, and 0.5M sucrose and stored in liquid nitrogen. Following thawing, embryos were directly transferred to recipientsthrough an open-pulled straw following an inguinal laparotomy. Sixteen recipients were treated with 20 µg Gonadorelin immediately after embryo transfer. Results: Onset and duration of estrus in donor and recipient ewes were 30.2 ± 0.8, 27.9 ± 0.6, and 33.7 ± 0.4, 27.50 ± 0.42 h, respectively. Corpora lutea number and recovered embryos/donor were 8.47 ± 0.68 and 6.93 ± 0.57, respectively. 85.7% of donors responded to superovulation treatment, and the embryo recovery rate was 82.5%. Grade 1 embryos per donor (5.5 ± 0.8) were significantly higher (p < 0.05) than all other grades. Pregnancy rates in recipients treated with Gonadotrophin-releasing hormone (GnRH) and without GnRH treatment were 62.5% and 56.6%, respectively. The respective lambing rates were 80% and 76.5%. Conclusion: These findings indicate the potential on-farm application of direct transfer of vitrified embryos in facilitating a MOET program for genetic improvement of sheep in Bangladesh. J. Adv. Vet. Anim. Res., 12(3): 1081–1086, September 2025 http://doi.org/10.5455/javar.2025.l968